Dampak Inklusi Keuangan dan Efektivitas Manajemen UMKM terhadap Peningkatan Literasi Keuangan (Studi pada UMKM Kota Binjai) - Julita, Julita (Maneggio: Jurnal Ilmiah Magister Manajemen, 2025)
This study was conducted to examine the impact of financial inclusion and the effectiveness of MSME management on improving financial literacy. This research is a quantitative study with data collection techniques using printed questionnaires and online questionnaires. The population and sample in this study were taken from 205 Micro, Small, and Medium Enterprises (MSMEs) in Binjai City, through collaboration using a cluster sampling approach in 5 sub-districts in Binjai City, as well as random sampling based on the criteria of type, duration, and average level of business profit. Primary data processing used SEM (Structural Equation Modeling) assisted by SEM-Lisrel software. The results of the study taken from the journal "Financial Management Model Based on Financial Literacy and Financial Inclusion: Study on MSMEs in Binjai City" show that financial literacy has a positive effect on financial inclusion and financial management. Financial inclusion has also been shown to improve financial management. In addition, financial inclusion mediates the relationship between financial literacy and financial management.